The Role of Coastal Women in Improving the Family Economy in Namlea Ilath Village Batabual District, Buru Regency - Izaac Tonny Matitaputty; Terezia Valency Pattimahu; Sartika Ode; M Sangadji (Trunojoyo University of Madura, 2023)
This study aims to determine how the role of coastal women in improving the family economy and the impact of the dual role. This study uses a descriptive type of research that describes a situation in a qualitative approach. In this study using data analysis techniques Miles and Huberman models such as: data reduction, data presentation and verification, as well as data collection such as: observation, interviews, and documentation.The results of this study indicate that along with economic and population growth, it will certainly have an effect on household needs which continue to increase. This can be seen from the increase in the price of goods, the reduced interest from consumers or customers, the uncertain income of fishermen and farmers caused by changes in weather, the cost of children's education and the cost of other household needs. From this problem, if the fishing communities and their farmers only rely on their basic work, then they can only pay for their daily meals and cannot save money to pay for their children's education. so that women take on a dual role that is needed in the family, namely as a side job to help husbands in meeting all the economic needs of the family.